Design and experiment of pneumatic seed clearing mechanism for pin-hole tube wheat plot precision sowing device - Zhang, Xirui; Yang, Youming; Wang, Qingjie; Li, Hongwen; Zhang, Zhifu; Liu, Junxiao (International Journal of Agricultural and Biological Engineering, 2023)
For the problem that when wheat is sucked up by the air suction method, the seeds are gathered in a small area, making it difficult for the contact seed cleaning mechanism to clean the seeds. The mechanism of seed cleaning airflow on wheat seed was studied, the flow velocity distribution relationship of the jet section was defined, the mathematical model of the jet velocity of circular and plane sections was established, and the key factors that could have a significant influence on seed cleaning effect were explored. A non-contact positive pressure air flow seed cleaning method was proposed. After theoretical calculations, it is concluded that the core section lengths of the circular section jet and the inline jet are 24.8 mm and 28.8 mm, respectively. The clearing distance is set to 20 mm. Through the single-factor test, the best air tube nozzle shape was clarified as a vertical inline nozzle. The angle of seed cleaning, the air velocity of seed cleaning, and the negative supply pressure were selected as influencing factors, and the seed leakage index, seed reabsorption index, and seed qualification index as the evaluation indicators to conduct a 3-factor 5-horizontal rotation test. A mathematical regression model of influencing factors and evaluation indexes was established to analyze the influence of these factors and indexes. The optimal operation parameters were obtained as the seed cleaning Angle of 19°, the seed cleaning air velocity of 58 m/s, and the negative pressure of 8.5 kPa. Under the optimal parameters, the seed leakage suction index is 8.23%, the seed reabsorption index is 0.33%, and the seed qualification index is 91.44%, which meets the design requirements. Keywords: wheat, precision seed-metering device, clearing, seed, positive pressure airflow, jet flow field DOI: 10.25165/j.ijabe.20231604.8006 Citation: Zhang X R, Yang Y M, Wang Q J, Li H W, Zhang Z F, Liu J X. Design and experiment of pneumatic seed clearing mechanism for pin-hole tube wheat plot precision sowing device. Int J Agric & Biol Eng, 2023; 16(4): 85-95